2018
DOI: 10.1002/jbm.a.36452
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on cytotoxicity and genotoxicity of the hydroxyapatite‐bioactive glass and fluorapatite‐bioactive glass nanocomposite foams as tissue scaffold for bone repair

Abstract: Considering to the possibility of cellular and genetic damage by the implant materials in the patient and the clinician, the safety of the biomaterials should be evaluated. The purpose of this study was to compare the cytotoxicity and genotoxicity induced by two nanocomposites, hydroxyapatite/bioactive glass (HA/BG) and fluorapatite/bioactive glass (FA/BG) in vitro. Biomaterial extracts (BMEX, 100%) were prepared by incubating 100 mg/mL of each biomaterial powder in complete culture medium (RPMI1640 + 10% FBS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
3
8
0
Order By: Relevance
“…As a traditional coating material for dental implants, HA is widely recognized as a type of bioactive material with good biocompatibility and bone conductivity. A large number of studies have reported that HA has good biocompatibility and can meet the requirements of implant materials, which is consistent with the results of our study [ 33 , 34 ]. Plasma sprayed HA-coated implants are commonly used.…”
Section: Discussionsupporting
confidence: 93%
“…As a traditional coating material for dental implants, HA is widely recognized as a type of bioactive material with good biocompatibility and bone conductivity. A large number of studies have reported that HA has good biocompatibility and can meet the requirements of implant materials, which is consistent with the results of our study [ 33 , 34 ]. Plasma sprayed HA-coated implants are commonly used.…”
Section: Discussionsupporting
confidence: 93%
“…The results obtained are in good agreement with studies presented by Cai et al (2007) who showed that hydroxyapatite crystals affects the metabolic activity of U-2 OS [56]. Additionally, Seyedmajidi et al [59] showed that hydroxyapatite/bioactive glass (HA/BG) at certain concentration may have a cytotoxic effect, and decrease metabolic potential of Saos-2. In turn, in this study we have shown that mitochondrial metabolism of MG-63 is accelerated in cultures on 10 wt % 3 mol % Eu 3+ : nHAp/PLLA scaffold.…”
Section: Discussionsupporting
confidence: 89%
“…Seyedmadiji et al [85] investigated the functionality of HA/bioactive glass (BG) and fluorapatite (FA)/BG materials. They also employed the Comet assay to investigate potential genotoxic effects on Saos-2 cells and found a dose-dependent increase in DNA degradation, but within the limits of safety (therefore, below any threshold of genotoxicity).…”
Section: Biocompatibility Assessment Of Cap-based Bioceramicsmentioning
confidence: 99%